Evaluation of adoption rate of frozen sexed semen artificial insemination technology adoption in Palang Village, Tuban Regency, East Java - Rizki Prafitri; Priyo Sugeng Winarto; Aulia Puspita Anugra Yekti; Trinil Susilawati; Kuswati Kuswati (Faculty of Animal Science, Universitas Brawijaya, 2021)
A research group of Animal Science Faculty of Brawijaya University introduced and implemented Frozen sexed semen Artificial Insemination to 120 beef cattle farmers in Palang Village, Tuban Regency, East Java, from 2017 to 2019. The result of the program reported that the success rate of the technology is quite high, with the birth rate of male claves up to 80%. However, farmers’ adoption rate of the technology was relatively low. This research aims to evaluate factors that affected the adoption rate including the technology, characteristics of respondents, and the extension agents. Primary data were collected through a census of 120 farmers involved in the program and in-depth interviews with stakeholders. Secondary data were collected through related documents including reports of the programs, Statistics, and other related documents. This research utilized Quantitative and qualitative analyses. Data of the study indicated that respondents have neutral perceptions of the Frozen Semen Sexing Artificial Insemination. Although male calves relatively have a higher price, more than 50% of respondents did not expect specific sexing for the calves. In-depth interview data revealed that the success of the Artificial insemination technology is more valuable for the farmers rather than the sexing. Characteristics of respondents and the extension agents played significant roles in the adoption rate of the Frozen Sexed Semen Artificial Insemination technology adoption in Palang Village, Tuban Regency, East Java.